Contemporary Challenges and Practices in Logistics and Supply Chain Management - Abdullah Okumus; Ebru Demirci; Muhammet Gul (Istanbul University Press, 2024)
In recent years, extraordinary developments such as global epidemics, war and other humanitarian crises that the world has experienced have caused some recessions and difficulties in logistics and supply chains as well as in all sectors. While the world is making calculations of returning to its old order, new concepts and issues in logistics and supply chain management are on the agenda of both researchers and practical industry environments. For this reason, the idea of this book has emerged in order to bring these new concepts, models, and good practice examples that are new and candidate to application in these two subjects, such as logistics and supply chain management, which require an interdisciplinary view. With this book, contemporary challenges and applications in logistics and supply chain have been discussed from the perspective of different disciplines such as marketing, management science, social sciences, engineering and law. Many issues such as supply chain analytics, new developments in logistics and human resources in the supply chain, new concepts in sustainable and reverse logistics (such as sustainable supplier selection, risk management, resilience, service quality), integration of the internet of things into logistics and supply chain, evaluation of sustainable practices and company profitability of transportation and logistics businesses, and the situation of freight forwarders in logistics and transportation law have been discussed through this book, and a guide has emerged that will benefit both the academia and industry. We are very thankful to the Istanbul University Press team for making this book publication smooth and successful. We thank all the authors, who are the true architects of the success of our book project, and the reviewers for their valuable comments, contributions, patience and cooperation. Finally, we, as the three editors of this book, are grateful to our families for their constant love, patience and support. Without their unique support, we would not have been able to complete this book. With the best wishes that the book will be useful to all concerned.
Keywords: 650